Interaction between bacterial microbiota and nematode parasite communities in sheep’s gastrointestinal tract - Maté, María Laura (2024)
The economic impact of gastrointestinal (GI) nematode infections on livestock production iswell documented worldwide. Increasing evidence supports the hypothesis that parasite colonization induces significant changes in the GI tract environment and, therefore, in the landscape where the microbiota and parasites occur. Understanding the interactions betweenbacterial and parasite populations in the digestive tract of livestock may be useful to designparasite control strategies based on microbiota modification. The aims of this work were toinvestigate the impact of the oxytetracycline-mediated manipulation of the gut microbialcommunity on the composition of GI nematode populations in naturally infected sheep andto explore changes in the GI microbial communities after nematode population treatmentwith the anthelmintic compound monepantel. Extensive manipulation of the GI microbiotawith a therapeutic dose of the long-acting oxytetracycline formulation did not induce significant changes in the GI nematode burden. The gut microbiota of treated animals returned tocontrol levels 17 days after treatment, suggesting strong resilience of the sheep microbialcommunity to antibiotic-mediated microbiota perturbation. A significant decrease of the bacterial Mycoplasmataceae family (Log2FC = -4, Padj = 0.001) and a marked increase of theMethanobacteriaceae family (Log2FC = 2.9, Padj = 0.018) were observed in the abomasumof sheep receiving the monepantel treatment. While a comprehensive evaluation of theinteractions among GI mycoplasma, methanobacteria and nematode populations deservesfurther assessment, the bacteria-nematode population interactions should be included infuture control programs in livestock production. Understanding how bacteria and parasitesmay influence each other in the GI tract environment may substantially contribute to theknowledge of the role of microbiota composition in nematode parasite establishment andthe role of the parasites in the microbiota composition.